Nurses' perceptions, experiences and involvement in the provision of end-of-life care in acute hospitals: A mapping review of research output, quality and effectiveness. (October 2021) - Shepherd, Jan; Waller, Amy; Sanson-Fisher, Rob; Clark, Katherine
Abstract: Background: Safe and high-quality end of life care is not always achieved in acute care hospitals. Nurses represent a key source of information about current practice, and active participants in interventions to improve end of life care in these settings. Examining the volume, type and quality of publications in this field can help to determine whether research is following a natural scientific progression to inform best-practice end of life care. Aims: To systematically review: (i) whether the volume and type of publications (i.e. measurement, descriptive or interventions studies) examining nurses' perceptions of, and involvement in, end-of-life care delivered in acute hospitals changed over time (i.e. since 2000); (ii) the proportion of intervention studies involving nurses that meet Risk of Bias research design criteria; and (iii) the effectiveness of intervention studies that met minimum Risk of Bias criteria. Methods: MEDLINE, Embase, CINAHL, and PsychInfo were searched for data-based papers published in English between Jan 2000 and Dec 2020. Studies were included if they focused on nurses' perceptions of, or role in, the provision of end-of-life care in hospitals. Eligible papers were classified as descriptive, measurement or intervention studies. Intervention studies were assessed against the Risk of Bias methodological criteria for research design, and their effectiveness examined. Results: A total of 131 papers met eligibility criteria for inclusion in the review. The number increased by 31% in each time period ( p  < 0.0001). Most studies were descriptive ( n  = 70; 53%), 11 were measurement studies (8%), and the remainder were intervention studies ( n  = 50; 38%). Thirteen intervention studies (26%) met eligibility criteria. Methodological quality of the eligible intervention studies was variable. Randomisation and blinding of outcome assessors were the domains of greatest concern. Results were variable, with larger, system-wide interventions that incorporated the expertise of the multidisciplinary healthcare team showing the most promise. Conclusion: There is an increasing number of studies examining nurses' perceptions of, and involvement in, end-of-life care delivered in acute hospitals. The difficulties of conducting intervention research in this field mean that many studies are descriptive in nature. Given the importance of intervention research in establishing causal relationships, larger-scale intervention studies are essential to improving the quality of end-of-life care provided to patients dying in hospital.